Exploring household food waste within informal settlements in the Fezile Dabi District in the Free State - Ebuzeme, Promise (Vaal University of Technology, 2025)
Household food waste is a major problem caused by factors like poor planning, overserving and careless buying habits. It contributes to greenhouse gas emissions and wastes energy in the food supply chain. High levels of food insecurity in South Africa (SA) raise concerns about the quantity of food wasted daily and annually. Global efforts to eradicate hunger by 2030 are hindered by conflicts, economic changes, unstable climate and growing inequality. Malnutrition and food insecurity are major concerns for governments and policymakers around the world, particularly for the impoverished who have limited access to food. Intense conflict, abrupt changes in the economy, extreme and unstable climate and growing inequality are impeding global attempts to eradicate hunger by 2030. Food availability and status are impacted by factors like war, natural resource limitations and climate change. Physical isolation, poor infrastructure, limited market access and susceptibility to disease outbreaks make meeting the world's food needs more challenging for both domestic and foreign nations. The South African government, represented by the Department of Environment, Forestry and Fisheries (DEFF), is obligated to promote the adoption of solutions to halve waste in half. The study's main objective is to explore household food waste within the informal settlements of the Fezile Dabi district, managed under the Metsimaholo municipality, to identify the most common food items wasted and the reasons for the household food waste. The study followed a non-experimental descriptive quantitative design. The study population included individuals who were above 18 years of age and responsible for cooking in the households or contributed to the decisions made about the types of foods purchased or prepared within the selected communities in the Free State province, specifically the Fezile Dabi district, managed by the Metsimaholo municipality. For this study, four areas were identified and selected: Sasolburg with 341 participants, Deneysville with 21 participants, Kragbron with 12 participants and Oranjeville with 59 participants. A total of 433 questionnaires were completed across the four communities. The questionnaire comprised 60 questions divided into three sections, namely demographics, common food items wasted and reasons for food waste. The questionnaire was piloted, the fieldworkers were recruited and trained to assist with the study. The fieldworkers were divided into groups, each group overseeing a particular street. They approached each house, greeted the person who came to the gate and if the individual was over 18, requested their consent. Participants were asked to sign the consent form before the questionnaire was administered. The study reveals that food waste is primarily caused by inadequate storage conditions, load shedding and neglect. High unemployment rates were observed, with 47 percent of respondents being unemployed. While most participants have some level of education, school dropout rates appear significant. Nearly half of the respondents across the four communities have three to four members per household, with some (20%) report having five to six members. Many rely on public transport, while the majority (81%) rely on electricity for food preparation. A lack of cooking knowledge contributes to 62 percent of household food waste, with 81 percent relying on electricity. Additionally, 49.5 percent of respondents believe that inadequate storage affects the type and amount of food wasted. The study also shows that 62.8 percent of households consume leftovers one to three times per week. Maize meal, bread and potatoes are the most wasted foods, followed by beef intestines and steak cuts. Bananas are the most wasted fruit, while tomatoes and carrots are the most discarded vegetables. Majority of the participants (n=325) responded to not wasting any form of alcoholic beverage during a week. Respondents from all four communities reported disposing of more than one litre of non-alcoholic liquid waste per week. Only 28.8 percent of respondents applied some form of recycling or reuse of leftovers and 57 percent were unaware of waste management strategies in the region. Only 22.7 percent understood that spoiled food could be repurposed instead of discarded. The study suggests that while some communities are aware of food waste prevention, they need better information on how to solve the issue. Educational strategies include reducing excessive purchases, properly managing leftovers, using refrigeration properly and understanding food spoilage. With the high levels of food insecurity within South Africa, household food waste requires action to be minimised/prevented and reduce the impact on society, the economy and the environment. The results from this study are like those in other regions in South Africa and around the globe. Practical approaches and campaigns must be developed to guide household consumers in reducing food waste. Further recommendations include educating households on food preservation methods, including pickling.
MM (FSM) (Faculty of Human Sciences, Food Service Management, Department of Tourism and Integrated Communication), Vaal University of Technology.
Keywords: Household food waste; Leftovers; Informal communities; Common foods; Poverty; Food insecurity; Dissertation, Academic -- South Africa.; Food waste.